KETERAMPILAN BERCERITA SISWA KELAS VII SMP NEGERI 2 KEMBAYAN DENGAN MEDIA BONEKA - Yuniwati, Yuniwati; Martono, Martono; Salem, Laurensius (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractStorytelling skills have a very important role for students to carry out learning activities. Storytelling skills need to be mastered by students. The results of interviews and observations made with Indonesian Language and Literature teachers at SMP Negeri 2 Kembayan 2014/2015 Learning year, there were several problems in the learning process of storytelling. The problem was related to the process and learning outcomes of students who still have not reached the value of completeness. This problem arises because of several factors. One of them, namely the selection of learning methods that were less varied. Teachers tend to use lecture or conventional methods in the learning process so that the learning process seems monotonous and boring for students. The efforts carried out in this study were to apply puppet media.Â Keywords: Ability, Puppet media, Storytelling.